In vitro development of Haplorchis taichui (Trematoda: Heterophyidae) - Chaithong U. (2014)
Newly excysted metacercariae of Haplorchis taichui were cultured in a candle jar set at 37%deg;C. Both monophasic culture media [0.85% NaCl, RPMI 1640, RPMI 1640+10% fetal calf serum (FCS)] and diphasic culture media [RPMI 1640 + egg yolk agar, RPMI 1640 + 5%, 10% or 15% blood in blood agar (BA), RMPI 1640 + 5%, 10% and 15% FCS with 5% blood in BA] were used in vitro. Parasites survived for only 1 day in 0.85% NaCl without any development. In RPMI 1640 with egg yolk agar and RMPI 1640 + 5%, 10% FCS, the parasite survived for 3-5 days. In contrast, worms survived for 12-14 days in RPMI 1640 with blood agar without any change in result in a different concentration of blood in BA. The ovary and testes were observed after 3 days incubation in this media. Nevertheless, only 1 parasite in RPMI 1640 with 15 % blood in BA had vitellaria and eggs at day 6. RPMI 1640 with blood agar can be used as short-term maintenance for the in vitro culture of H. taichui. However, further studies are needed.